Host Genomics of the HIV-1 Reservoir Size and Its Decay Rate During Suppressive Antiretroviral Treatment. (1st December 2020) - Thorball, Christian W.; Borghesi, Alessandro; Bachmann, Nadine; Von Siebenthal, Chantal; Vongrad, Valentina; Turk, Teja; Neumann, Kathrin; Beerenwinkel, Niko; Bogojeska, Jasmina; Roth, Volker; Kok, Yik Lim; Parbhoo, Sonali; et al.
Abstract : Background: The primary hurdle for the eradication of HIV-1 is the establishment of a latent viral reservoir early after primary infection. Here, we investigated the potential influence of human genetic variation on the HIV-1 reservoir size and its decay rate during suppressive antiretroviral treatment. Setting: Genome-wide association study and exome sequencing study to look for host genetic determinants of HIV-1 reservoir measurements in patients enrolled in the Swiss HIV Cohort Study, a nation-wide prospective observational study. Methods: We measured total HIV-1 DNA in peripheral blood mononuclear cells from study participants, as a proxy for the reservoir size at 3 time points over a median of 5.4 years, and searched for associations between human genetic variation and 2 phenotypic readouts: the reservoir size at the first time point and its decay rate over the study period. We assessed the contribution of common genetic variants using genome-wide genotyping data from 797 patients with European ancestry enrolled in the Swiss HIV Cohort Study and searched for a potential impact of rare variants and exonic copy number variants using exome sequencing data generated in a subset of 194 study participants. Results: Genome-wide and exome-wide analyses did not reveal any significant association with the size of the HIV-1 reservoir or its decay rate on suppressive antiretroviral treatment. Conclusions: Our results point to a limited influence of human genetics on the size of the HIV-1 reservoir and its long-term dynamics in successfully treated individuals. Abstract : Supplemental Digital Content is Available in the Text.